2021
DOI: 10.1097/md.0000000000026533
|View full text |Cite
|
Sign up to set email alerts
|

Early use of tocilizumab in patients with severe pneumonia secondary to severe acute respiratory syndrome coronavirus 2 infection and poor prognostic criteria

Abstract: The coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2, keeps spreading globally. Evidence suggests that a subgroup of patients with severe symptomatology might have cytokine storms, which increases mortality. The use of interleukin-6 (IL-6) inhibitors may help in controlling the pathological immune response to the virus. Tocilizumab, a monoclonal antibody against IL-6, stands as an optional treatment for COVID-19 patients presenting this inflammatory hyper-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
(70 reference statements)
0
7
0
1
Order By: Relevance
“…IL-6 plays a critical role in driving the pro-inflammatory acute phase of antiviral responses, as well as in switching the inflammatory response from an acute, neutrophil-driven response to an inflammatory response characterized by recruitment of monocytes and differentiation of macrophages (9). The complex role of IL-6 has made it difficult to decipher the involvement of IL-6 in the pathology of Multiple studies have assessed the benefit of tocilizumab, an anti-IL-6 receptor (IL-6R) alpha antibody, in patients hospitalized with COVID-19 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19), and have individually shown mixed results, possibly due to heterogeneity of the patient population, timing of treatment, shifting standard of care (e.g., systemic corticosteroids), and insufficient sample size. In particular, COVACTA was a global, double-blind, randomized, placebo-controlled, phase 3 trial of 452 patients hospitalized with COVID-19 randomized to tocilizumab or placebo treatment (12).…”
Section: Introductionmentioning
confidence: 99%
“…IL-6 plays a critical role in driving the pro-inflammatory acute phase of antiviral responses, as well as in switching the inflammatory response from an acute, neutrophil-driven response to an inflammatory response characterized by recruitment of monocytes and differentiation of macrophages (9). The complex role of IL-6 has made it difficult to decipher the involvement of IL-6 in the pathology of Multiple studies have assessed the benefit of tocilizumab, an anti-IL-6 receptor (IL-6R) alpha antibody, in patients hospitalized with COVID-19 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19), and have individually shown mixed results, possibly due to heterogeneity of the patient population, timing of treatment, shifting standard of care (e.g., systemic corticosteroids), and insufficient sample size. In particular, COVACTA was a global, double-blind, randomized, placebo-controlled, phase 3 trial of 452 patients hospitalized with COVID-19 randomized to tocilizumab or placebo treatment (12).…”
Section: Introductionmentioning
confidence: 99%
“…81% male, 25% hypertensive, 27% diabetic 4—5 Tocilizumab 8 mg/kg IV up to maximum of 800 mg IV N = 49 Hydroxychloroquine, azithromycin, beta-lactams, lopinavir-ritonavir N = 47 November 2020 Tsai et al [ 47 ] Single-centre, USA 132 Mean age 62.38 ± 13.49 in treatment group, 61.35 ± 16.09 in SOC group 73% male, 54.6% hypertensive, 30.3% diabetic 4—5 Tocilizumab 80.3% received 400 mg while 19.6% received > 400 mg. Four patients received second dose N = 66 Hydroxychloroquine, azithromycin, antibiotics (cephalosporins, piperacillin/tazobactam) N = 66 December 2020 Tian et al[ 48 ] Multi-centre, China 195 Median age 69.0 [62.0 – 75.0] 67% male,52.8% hypertensive, 16.9% diabetic 4—5 Tocilizumab 4 -8 mg/kg IV up to 800 mg IV N = 65 Antibiotic therapy, Antiviral therapy (lopinavir-ritonavir, ganciclovir, oseltamivir) N = 130 January 2021 Rajendram et al[ 49 ] Multi-centre, USA 444 Mean age 64 ± 12 in treatment group, 64 ± 13 in control group.33% diabetic, 4—5 Tocilizumab Doses not stated N = 102 Remdesivir, lopinavir-ritonavir, hydroxychloroquine, azithromycin N = 342 April 2021 Huang et al[ 50 ] Single centre, USA 96 Mean age 66.59 ± 19.10 in treatment group, 63.22 ± 16.29 in SOC group. 80% male, 60% hypertensive and 49% diabetic in treatment group 4—5 Tocilizumab A single 400 mg IV infusion N = 55 Hydroxychloroquine, remdesivir, azithromycin N = 41 June 2021 Sanchez-Rovira et al[ 52 , 51 ] …”
Section: Resultsmentioning
confidence: 99%
“…Of these 24 studies, seven studies that showed favourable outcomes involved tocilizumab [ 30 , 32 , 37 41 ]. The one study involving dexamethasone, Fusina et al [ 51 ] failed to reduce COVID-19 mortality (OR 1.28 95% CI 0.99 -1.67) while the two studies included that used methylprednisolone alone (Mikulska et al, OR 0.32, 95% CI 0.10 – 1.03; Nelson et al, OR 0.42 95% CI 0.16—1.15) did not show significant mortality reduction [ 43 , 44 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in fiber composition of lung tissue, and the occurrence of hypoxemia, hypoxemia and uncontrolled lung inflammation can lead to lung tissue injury, and in severe cases, to life threatening septic shock. 14 – 1 caused by severe acute respiratory syndrome coronavirus 2, keeps spreading globally. Evidence suggests that a subgroup of patients with severe symptomatology might have cytokine storms, which increases mortality.…”
Section: Discussionmentioning
confidence: 99%